Levosimendan's effect on platelet function in a rat sepsis model - Bent, Franziska; Plaschke, Konstanze (Platelets, 2012)
Although studies have evaluated the efficacy of levosimendan in heart failure during sepsis, it still is a subject of controversy whether levosimendan produces an effect on platelets. In this study, the short- and long-term effects of levosimendan on platelet aggregation were investigated in untreated animals and in a rat model of sepsis. Therefore, adult rats (n = 40) were randomly divided into four groups with n = 10 per group: (I) sham, (II) levosimendan (bolus 53 µg/kg + 285 µg/kg/hour, intravenously (i.v.) injected), (III) LPS (lipopolysaccharide, 8 mg/kg body weight intraperitoneally injected), and (IV) LPS + levosimendan. Levosimendan was given 24 hours after LPS injections. The number of platelets was determined. Platelet aggregation was measured using venous blood from rats 10 minutes and 5 days after levosimendan application with Dynabyte Multiplate system. Aggregation responses were evaluated with adenosine diphosphate (10 µM) and collagen (5 µg/ml). In addition to clinical dosage, the in vitro effect of high-dosage levosimendan on platelet function was investigated.The results clearly showed that LPS significantly reduced the platelet aggregation 1 day after injection compared to controls; 6 days after LPS, a marked increase (p < 0.01) was noted. This result is associated with numbers of platelets. Levosimendan (bolus 53 µg/kg + 285 µg/kg/hour i.v.) had no significant effect on the platelets of rats in contrast to the high-dosage in vitro findings. Thus, the in vivo use of levosimendan does not affect blood coagulation significantly in this rat model. This also applies under the conditions of decreased and increased numbers of platelets during mild sepsis.
Gesehen am 12.04.2018